Efficient Temporal Coding in the Early Visual System: Existing Evidence and Future Directions - Price, Byron H.; Gavornik, Jeffrey P. (Frontiers in Computational Neuroscience, 2022)
While it is universally accepted that the brain makes predictions, there is little agreement about how this is accomplished and under which conditions. Accurate predictions require neural circuits in the brain to implement some form of coding that stores spatiotemporal relationships based on environmental statistics, but it is not obvious what this code should look like. Information theory provides a mathematical formalism that can be used to measure the efficiency and utility of different coding schemes for data transfer and storage. This theory shows that codes become efficient when they remove predictable, redundant spatial and temporal information. Efficient coding has been used to understand retinal computations and may also be relevant to understanding more complicated temporal processing in visual cortex. However, the literature on efficient coding in cortex is varied and can be confusing since the same terms are used to mean different things in different experimental and theoretical contexts. In this work, we attempt to provide a clear summary of the theoretical relationship between efficient coding and temporal prediction, and review evidence that efficient coding principles explain computations in the retina. We then apply the same framework to computations occurring in early visuocortical areas, arguing that data from rodents is largely consistent with the predictions of this model. Finally, we review and respond to criticisms of efficient coding and suggest ways that this theory might be used to design future experiments, with particular focus on understanding the extent to which neural circuits make predictions from efficient representations of environmental statistics.